The dish ran away with the spoon : revisiting unprovenienced foodways artifacts from eighteenth century Spanish fleet shipwrecks - Thomas, Olivia L. (East Carolina University, 2017)
The Spanish empire was the first European power to establish permanent settlements that flourished as New World colonies on several of the Caribbean islands and coasts of North America. The distance between Spain and the colonies led to differences in the lifestyles and customs which developed in these frontier spaces. Archaeological investigations both on land and underwater have yielded a considerable amount of material culture reflecting Spanish life in the territories of Florida and the Caribbean. This thesis will examine artifacts associated with Spanish colonial "foodways" in two shipwreck assemblages from the early eighteenth century coast of Florida. These foodways artifacts highlight societal and commercial trends of the eighteenth-century Spanish maritime empire.
Keywords: Maritime history; Colonial Spanish America; foodways; cutlery; Material culture--Florida--History--18th century; Material culture--Spain--History--18th century; Shipwrecks--Florida; Shipwrecks--Caribbean Area; Underwater archaeology--Florida